A Hydrological–Energy Balance Model to Assess Land Surface Temperature at the Urban Scale: The Case Study of Milano, Italy - Sonia Morgese; Wenchuang Zhang; Francesca Casale; Daniele Bocchiola (Meteorological Applications, 2025)
ABSTRACT This paper provides a physically based approach to assess Land Surface Temperature (LST) in an urban context, to analyze the Surface Urban Heat Island Intensity (SUHII). We developed and tested a joint hydrological–energy balance model, Poli‐HE, to compute surface energy and mass fluxes between soil surfaces and shallow atmospheric layers in the city of Milano, Italy. Land Surface Temperature (LST) was calculated under given climate conditions and land cover, and spatially distributed with a resolution of 500 m. For mixed paved/green pixels, Vegetation Fraction (VF) was applied. Energy and water balances were integrated, linking water content and latent heat flux to LST. Data from 9 meteorological stations in Milano provided inputs of radiation, air temperature, precipitation, wind speed, and relative humidity during 2010–2022. LST estimated by MODIS satellite were used for model tuning, where the Poli‐HE model effectively replicated the spatial distribution of urban LST. During summer, when LST in Milano reaches +35°C, paved and green surfaces differ by about + 3.7°C, reaching up to + 4.5°C at times. The Poli‐HE outcomes indicate that the presence of green areas can provide a cooling effect and reduce LST, as also shown by satellite observations. Particularly, we showed that an increase of green share, ΔVF = + 10%, may correspond to a decrease of ΔLST = −0.26°C. Our quantitative approach may support urban authorities and professionals, providing a practical tool for current and future planning and projects for adaptation and mitigation under the framework of national and international efforts.